Ingerencje socjotechniczne w mechanizm społecznej aktywności - Czarnecka, Anna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
It is hardly a secret that modern democratic steering should melt into a natural course of events and make an impression of a cooperative partner system: the steering – the steered. In the scientific engineering approach to society a prodemocratic spark has appeared. This concerns the issue of society accommodating the changes (and not only the quality of such accommodation). What is meant here is the latest definition of social technique, developed by Piotr Pawe³czyk, who treats it as a process, i.e. a sequence of changes and states following in succession and organized in time.